If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 25x + 13 + -33x = 11 Reorder the terms: 13 + 25x + -33x = 11 Combine like terms: 25x + -33x = -8x 13 + -8x = 11 Solving 13 + -8x = 11 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-13' to each side of the equation. 13 + -13 + -8x = 11 + -13 Combine like terms: 13 + -13 = 0 0 + -8x = 11 + -13 -8x = 11 + -13 Combine like terms: 11 + -13 = -2 -8x = -2 Divide each side by '-8'. x = 0.25 Simplifying x = 0.25
| -6r-11r+4=-47 | | 4x+11=10x-1 | | 2x/5-x=x/15-4/3 | | 3x-3=-4x+32 | | 7x/11=5x/9+8 | | 3(v-3)-8v=1 | | 72=27+5x | | 18=-16t^2+35t-5.5 | | 4x^3-11x+5=0 | | 6(u+3)-8u=12 | | x(x+5)=20 | | -32=-6y+2(y-4) | | 8+40.8t-16t^2=10 | | -32=-6+2y(y-4) | | -7n-2=-48 | | (58x+65y)+(-9x+45y)= | | m(v-u)=I | | -18=5(x-6)-7v | | 5x+-3x=14 | | 36=4(y+6)-6y | | x+2+z=4 | | -21=-7x+2(x-3) | | 3x^2-70x+280=0 | | g/5=-16 | | 180=59 | | 7/5p+1/6p=3 | | a-17=-30 | | (-9x)-(6x)= | | 4+26/16+12+10+4= | | 5(-2n+4)=-10 | | 226-5x=40x+16 | | 4t^5(t-t^2+3t^3)= |